Children's Eye Movements, Miscue Analysis Patterns, and Retellings When Reading a Counterpoint Picture Book. (November 2016) - Liwanag, Maria Perpetua Socorro U.; Pelatti, Christina Yeager; Martens, Ray; Martens, Prisca
This study incorporated eye movement miscue analysis to investigate two second-graders' oral reading and comprehension of a counterpoint picture book. Findings suggest the second-graders' strategies when reading the written and pictorial text affected their comprehension as opposed to the number and location of their eye movements. Specifically, the data highlight the contextual nature of the counterpoint picture book and how the readers' strategies influenced the ways students navigated the text, what they fixated on while reading the written and pictorial texts, and the effects of these eye movement data on their comprehension. These results highlight the importance of young students' need to be able to distinguish and value the role of written and pictorial sign systems to facilitate success in an ever-expanding multimodal world.